Norm estimation for pre-Schwarzian and Schwarzian derivatives of some univalent functions - Wu, Xiaobin; Zhu, Wanghao (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5Our purpose is to obtain estimates for the norms of Schwarzian and pre-Schwarzian derivatives of strongly starlike functions and strongly convex functions of order $α$ and type $β.$ In addition, we present an example of a function $f \in S^*(α, β)$ that cannot be $k$-quasiconformally extended for any $k < α(1 - β).$